A Imprensa Negra Paulista e a educação: um movimento de resistência? - Sales, Ricardo Ramos (2015)
This dissertation is part of the concerns about racism forms and the historical resistance of the black population, to fighting against this phenomenon allows us to understand and formulate one of black identities in Brazil. To this end, the relations of power established between the different ethnic groups set up one of the strands to this analysis proposed by this work. We seek to understand the demonstrations and dissemination of black thought, the early twentieth century, through one of the instruments of this group, the Imprensa Negra Paulista. From our analysis, we identified two inherent aspects in the project of this press release: education and the fight against racism. However, the concept of education that black leadership, which was formed from the black press, demonstrated to be wide, while defending schooling at certain times, has generated non schooled actions that promoted equal education in others. It was precisely this expanded vision of education that allowed promote the combat against racism using the same weapon of the white people: the education. It is from these two aspects of the Imprensa Negra Paulista project that this work aims to contribute to the studies about race and ethnic issues of combating racism by black population